Analysis of psychological functioning of patients after their suicide attempts - Wierzbiński, Piotr; Talarowska, Monika; Chamielec, Marcelina; Mikołajczyk, Iwona; Strombek-Milczarek, Marta; Florkowski, Antoni (Current Problems of Psychiatry, 2012)
Suicide is a serious psychiatric problem. A deliberate act of taking their own lives by patients is a difficult and dramatic move. There has been ongoing discussion about causes of this phenomenon and they still have not been established unequivocally. There are numerous theories on the etiology of suicidal behaviors including a sociological theory, cognitive-behavioral theory and neurobiological theories.Material and methods. The research is based on the survey of the control group that consisted of 76 persons including 48 of those who had already attempted suicide. Among the group were also Lodz Babinski Hospital patients who attempted suicide recently or in the more distant past. Each patient did psychological CISS and IPSA-II tests.Results. A statistical analysis shows that patients attempting suicide differ in psychological traits from the rest of the control group. They have greater aggressive tendencies and difficulties in controlling emotions. They also tend to be less trusting.Conclusions. It is possible to attempt to prevent suicide. A psychological profile of those who attempt suicide could lead to a better understanding of mechanisms that underlie self-destructive actions and help identify a group of persons with a significantly greater suicidal behavior risk and apply preventive measures to those persons.